2022
DOI: 10.1371/journal.pcbi.1010295
|View full text |Cite
|
Sign up to set email alerts
|

What are housekeeping genes?

Abstract: The concept of “housekeeping gene” has been used for four decades but remains loosely defined. Housekeeping genes are commonly described as “essential for cellular existence regardless of their specific function in the tissue or organism”, and “stably expressed irrespective of tissue type, developmental stage, cell cycle state, or external signal”. However, experimental support for the tenet that gene essentiality is linked to stable expression across cell types, conditions, and organisms has been limited. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 54 publications
(113 reference statements)
2
45
0
3
Order By: Relevance
“…Nevertheless, these 53 genes were enriched in “basal cellular” functions including ribosomal activity, protein translation, and mitochondrial respiration (Fig. 2B), and in essential genes (lethal) as defined in partial 13 and full-genome RNAi screens 14,15 (Fig. 2C), two features in line with these genes being bona fide housekeeping genes.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Nevertheless, these 53 genes were enriched in “basal cellular” functions including ribosomal activity, protein translation, and mitochondrial respiration (Fig. 2B), and in essential genes (lethal) as defined in partial 13 and full-genome RNAi screens 14,15 (Fig. 2C), two features in line with these genes being bona fide housekeeping genes.…”
Section: Resultsmentioning
confidence: 86%
“…As scRNA-Seq is not yet available for C. elegans subject to perturbations (genetic, chemical, or other), we used time, in the form of a different life stage, as the alternative condition. Specifically, we looked at the overlap between genes consistently expressed (Gc <0.3) in young adults and a list of putative housekeeping genes reported for the C. elegans L2 larvae 14 . We found that all genes with high expression equality (Gs ≤0.2) and the majority of genes (319/390) with good expression equality (Gs <0.3) in the young adults were also consistently expressed across cell types in the L2 larvae (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we measured gene expression heterogeneity with two metrics, i.e., the proportion of housekeeping genes occupying all expressed genes and topology indices of the gene expression networks. Housekeeping genes (HKGs) are usually expressed at relatively constant rates for the basic molecular and cellular function of neurons 22 , 23 ; thus, the lower proportion of HKGs expressed in brain structures may suggest their higher functional diversity. Topological indices of the gene expression networks in brain structures, including mean path length, clustering coefficient and eigen entropy, offer possibilities to understand how genes work together to perform diverse functions 24 .…”
Section: Introductionmentioning
confidence: 99%